Optimization of tobacco leaves extraction process with microwave assisted extraction (MAE) as an antibacterial agents - Pranowo, Dodyk; Susanti, Sinta Defi; Mulyadi, Arie Febrianto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Tobacco (Nicotiana tabaccum L.) is an agricultural commodity in Indonesia, with production reaching 261.40 thousand tonnes in 2020.  Tobacco leaves contain flavonoids and alkaloids, which are helpful as antibacterial, antifungal, and anti-insect agents. This study aimed to optimize the extraction process of tobacco leaves as an antibacterial agent. The factors used were material-to-solvent ratio (w/v) and extraction time. The microwave-assisted extraction (MAE) was used, with the response surface methodology (RSM) for data processing. This study showed that  thematerial-to-solvent ratio and extraction time significantly affected the total flavonoid value, the extract inhibitory activity against S. mutans bacteria, and the extract yield. However, no significant effect was observed on the extract’s pH. The highest total flavonoid value, inhibitory activity, and pH were obtained from the treatment with a ratio of 1:2172 (w/v) and 6 minutes extraction time, giving an average value of 524.67 mg EQ/g, 22.4 mm, and 5.6, respectively. The highest yield of 4.61% was obtained from the treatment with a ratio of 1:5 (w/v) and 6 minutes extraction time. The optimal solution for the tobacco leaves extraction process was obtained from material-to-solvent ratio of  1: 2.6 (w/v) and 7 minutes of extraction time, giving the total flavonoids, inhibitory activity, pH, and yield of 428.4 mg EQ/g, 20.7 mm, 5.8, and 3.1%, respectively.